Pengaruh Kualitas Produk, Citra Merek dan Promosi terhadap Loyalitas Pelanggan pada Mie “SKR” Jember - Anggraini, Desta Rezzy; Faizah, Kurnia; Putri, Ghinadya Canceriani; Maulida, Nanda Kurniati; Qomariah, Nurul (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Noodles are a food product made from wheat flour without the addition of other food ingredients. Noodles are a substitute for rice which is popular with all groups, especially students. Noodle culinary delights have mushroomed under various brand names. This research aims to determine the influence of product quality, brand image and promotion on loyalty to